Blood flow restriction does not augment low force contractions taken to or near task failure. Issue 5 (27th May 2020) - Buckner, Samuel L.; Jessee, Matthew B.; Dankel, Scott J.; Mattocks, Kevin T.; Mouser, J. Grant; Bell, Zachary W.; Abe, Takashi; Bentley, John P.; Loenneke, Jeremy P.
Abstract: Low-load exercise performed to or near task failure appears to result in similar skeletal muscle adaptations as low-load exercise with the addition of blood flow restriction (BFR). However, there may be a point where the training load becomes too low to stimulate an anabolic response without BFR. This study examined skeletal muscle adaptions to very low-load resistance exercise with and without BFR. Changes in muscle thickness (MTH), strength, and endurance were examined following 8-weeks of training with a traditional high-load [70% 1RM, (7000)], low-load [15% 1RM, (1500)], low-load with moderate BFR [15%1RM + 40%BFR(1540)], or low-load with greater BFR [15% 1RM + 80%BFR(1580)]. 1RM strength changes were greater in the 7000 condition [2.09 (95% CI = 1.35–2.83) kg] compared to all low-load conditions. For isometric and isokinetic strength, there were no changes. For endurance, there was a main effect for time [mean pre to post change = 7.9 (4.3–11.6) repetitions]. At the 50% site, the mean change in MTH in the 7000 condition [0.16 (0.10–0.22) cm] was greater than all low-load conditions. For the 60% site, the mean change in MTH [0.15 (0.08–0.22)] was greater than all low-load conditions. For the 70% site there was a main effect for time [mean pre to post change = 0.09 (0.05–0.14 cm]. All groups increased muscle size; however, this response was less in all very low training conditions compared to high-load training. 1RM strength increased in the 7000 condition only, with no other changes in strength observed.